Increasing changes and challenges: School development 1986–2012 in the eyes of experienced upper secondary school teachers - Reynisdóttir, Árný Helga; Jóhannesson, Ingólfur Ásgeir (Menntavísindasvið Háskóla Íslands, 2016)
Since the passing of the Upper Secondary School Act in 2008 and the publication of the new National Curriculum Guide in 2011, both of which entailed significant changes for schools in Iceland, there has been an ongoing discussion about the ways in which the schools will develop. Basically, the new law grants schools and teachers autonomy to decide their own curricula. Instead of detailed instructions for every subject and subject area, the curriculum guide emphasizes six crosscurricular aims and defined levels of key competences. The authors interviewed twelve experienced teachers of equally many disciplines from four different upper secondary schools in Iceland. All of them started teaching before 1986, which is the year the first National Curriculum for upper secondary schools in Iceland was introduced. This study is a part of the first comprehensive study on upper secondary schools, which is titled Upper secondary school practices in Iceland: Teaching and learning – student engagement and initiative. The schools in the present study were randomly chosen from a stratified sample of the nine schools already chosen for the larger study but the selection of teachers was made by purposive sampling to ensure diversity. The aim of the study was to gain insight into what experienced upper secondary school teachers in Iceland think about changes in their work in the last 25 years. Particular attention was given to the (perceived) impact of different curricula on school development. This study is theoretically grounded in literature on accelerated social change and its wideranging effect on teachers’ work in the last few decades. It also looks into deeprooted hindrances to school development in upper secondary schools as well as identifying possibilities for teachers to cope with these changes. Results indicate some important changes in the work and role of upper secondary school teachers in the last quarter century. The interviewees talked about increasing pedagogical challenges due to changes in the student body and ...